A Girl Who is Smiling for no Reason: Gelastic Seizure- A Case Report - Paudel, Subodh Sharma; Agrawal, Nikhil (Journal of Nepal Paediatric Society, 2019)
Being a rare disorder, Gelastic seizure primarily presents as episodes of sudden occurrence of emotions usually associated with laugh or giggle due to facial contractions. A child presented with abnormal body movement in the form of smiling and uprolling of eyes, which was clinically diagnosed as gelastic seizure, a rare form of a very common presentation, epilepsy. The case is presented to highlight abnormal posturing and smiling episodes in a child can be a form of seizure episode, which generally presents with a diagnostic dilemma and therapeutic nightmare to the clinician.